Acoustic streaming caused by modulated sound and wave packets - Perelomova, A. (Archives of Acoustics, 2004)
The practical applications of sound relate to approximately periodic sounds. It is shown, that theoretical results of acoustic streaming based on a periodic everywhere sound, should be revised in spite of the experimental data demonstrating the essentially different velocities of streaming. A new approach, which allows evaluating the streaming caused by sound of every type, both periodic and non-periodic, leads to similar results. The results of numerical calculations of streaming caused by modulated sound and series of pulses are compared with those given by formulae for a periodic everywhere sound.